2015
DOI: 10.1007/s11999-015-4469-5
|View full text |Cite
|
Sign up to set email alerts
|

Which Fixation Device is Preferred for Surgical Treatment of Intertrochanteric Hip Fractures in the United States? A Survey of Orthopaedic Surgeons

Abstract: Background The best treatment for intertrochanteric hip fractures is controversial. The use of cephalomedullary nails has increased, whereas use of sliding hip screws has decreased despite the lack of evidence that cephalomedullary nails are more effective. As current orthopaedic trainees receive less exposure to sliding hip screws, this may continue to perpetuate the preferential use of cephalomedullary nails, with important implications for resident education, evidence-based best practices, and healthcare co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 34 publications
(55 reference statements)
3
84
1
2
Order By: Relevance
“…Some randomized clinical trials (RCTs) found no difference of implants in long-term functional outcome between the two devices [36]. Bhandari et al [7] reported that there were no large differences in IFF risk between the DHS and the PFNA.…”
Section: Introductionmentioning
confidence: 99%
“…Some randomized clinical trials (RCTs) found no difference of implants in long-term functional outcome between the two devices [36]. Bhandari et al [7] reported that there were no large differences in IFF risk between the DHS and the PFNA.…”
Section: Introductionmentioning
confidence: 99%
“…Our main reason for pursuing the use of short PFN was due to ease of insertion and reduced risk of femoral fracture. 9,12 A total of three previous studies found high TAD values to be a significant predictor of cutout in CM nails . 1,13,14 Yet more recent studies suggest that the cutout complication is very low even in patients with high TAD, if the lag screw was positioned inferior in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, though without literature support, many orthopedic surgeons believe CM nails are a superior construct to sliding hip screws. 9 This may be due to a shorter operating time, reduced visible intraoperative blood loss, and improved walking ability in unstable hip fractures associated with CM nail. 1 Current CM concepts may be classified as monoaxial and biaxial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But we can imagine-and have published-exceptions to this. We recently published a practice-pattern survey demonstrating that an important element of fracture care in practice deviates from solid clinical evidence [5]; in the future, we might also consider practice-pattern surveys that present some unexpected or counterintuitive findings, but by definition such studies are likely to be rare. [6], and ''Do Orthopaedic Surgeons Acknowledge Uncertainty?''…”
Section: P Resident Ronald Reagan Oncementioning
confidence: 99%